Iron supplementation regulates the progression of high fat diet induced obesity and hepatic steatosis via mitochondrial signaling pathways - Naho Kitamura (Nature Portfolio, 2021)
Abstract Disruption of iron metabolism is closely related to metabolic diseases. Iron deficiency is frequently associated with obesity and hepatic steatosis. However, the effects of iron supplementation on obesity and energy metabolism remain unclear. Here we show that a high-fat diet supplemented with iron reduces body weight gain and hepatic lipid accumulation in mice. Iron supplementation was found to reduce mitochondrial morphological abnormalities and upregulate gene transcription involved in mitochondrial function and beta oxidation in the liver and skeletal muscle. In both these tissues, iron supplementation increased the expression of genes involved in heme or iron–sulfur (Fe–S) cluster synthesis. Heme and Fe–S cluster, which are iron prosthetic groups contained in electron transport chain complex subunits, are essential for mitochondrial respiration. The findings of this study demonstrated that iron regulates mitochondrial signaling pathways—gene transcription of mitochondrial component molecules synthesis and their energy metabolism. Overall, the study elucidates the molecular basis underlying the relationship between iron supplementation and obesity and hepatic steatosis progression, and the role of iron as a signaling molecule.